COVID-19 associated myopathy. Issue 5 (11th October 2022) - Aschman, Tom; Stenzel, Werner
Abstract : Purpose of review: The global spread of severe acute respiratory syndrome coronavirus 2 resulted in many cases of acute and postacute muscular symptoms. In this review, we try to decipher the potential underlying pathomechanisms and summarize the potential links between viral infection and muscle affection. Recent findings: Disregarding single case studies that do not allow safe conclusions due to the high number of infections, histopathological evidence of myositis has only been reported in deceased individuals with severe COVID-19. Postacute myalgia and weakness seem to occur in a subset of patients up to one year after initial infection, reminiscent of postinfectious syndromes (PIS) described in prior epidemics and pandemics of the past. Summary: COVID-19 associated myopathy likely comprises different entities with heterogeneous pathomechanisms. Individual factors such as disease severity and duration, age, sex, constitutional susceptibilities, and preexisting conditions are important to consider when formulating a diagnosis. Persisting symptoms show overlapping features with PIS or postintensive care syndrome. In lack of strong evidence for a direct infection of myocytes, inflammatory myopathies associated with COVID-19 are presumably immune-mediated. Differential diagnosis of rheumatological and nonmuscular neurological origin coinciding with the infection need to be considered, due to the extremely high numbers of newly occurring infections the last 2 years.